TINJAUAN FAKTOR–FAKTOR YANG MEMPENGARUHI PEMILIHAN MODA MENUJU TEMPAT KERJA MENGGUNAKAN METODE ANALYTIC HIERARCHY PROSES - Nur Alim Dewa; Lambang Basri Said; Ilham Syafei (Ikatan Dosen Menulis, 2023)
Mode selection can be said to be the most important stage in transportation planning. Mode selection occurs as a result of the need for movement, and movement occurs because of the process of meeting those needs. The aim is to analyze the factors that influence the choice of mode in traveling to work in Makassar City, and to analyze the mode of transportation chosen by civil servants who are known to travel to work in Makassar City. data collection used in this study is a questionnaire survey method, interviews, observation, documentation. From the results that people's perceptions of public and private transportation services, namely from the survey results, it can be seen that of the 100 respondents the satisfaction value resulting from CSI calculations for public or private transportation is 78% and the safety factor for safety and crime in using public transportation or private transportation that is 63%.